Przywództwo w Unii Europejskiej - Sielski, Jerzy (Przegląd Politologiczny, 2018)
The current financial crisis has significantly highlighted the issue of leadership in the European Union. The topic is both timely and worthy of analysis. The author tries to outline the theoretical approach to political leadership with regard to the current political scene in the European Union. A politician has to meet four criteria to be deemed a leader: his decisions are strategic, they exert permanent influence, he has a sufficient political background, and he has the highest position in a given political composition. The author makes the following hypothesis: on the basis of factor analysis (as regards the four factors above) only two current politicians are the true leaders of the EU, namely the Chancellor of Germany, Angela Merkel, and the President of France, Francois Hollande. Both politicians meet the four attributes presented gabove to at least the minimum degree, thus becoming (international) EU leaders. The paper also discusses the issue of distinguishing between an (international) statesman and (international) leader.